2022
DOI: 10.48550/arxiv.2204.10935
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Certifiable Robot Design Optimization using Differentiable Programming

Abstract: There is a growing need for computational tools to automatically design and verify autonomous systems, especially complex robotic systems involving perception, planning, control, and hardware in the autonomy stack. Differentiable programming has recently emerged as powerful tool for modeling and optimization. However, very few studies have been done to understand how differentiable programming can be used for robust, certifiable end-to-end design optimization. In this paper, we fill this gap by combining diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…It has demonstrated that it is more than just a compilation of machine learning algorithms [109]. DP can be applied to various types of robots [110], including mobile robots, manipulators, and humanoid robots. DP can be used for tasks.…”
Section: Statementioning
confidence: 99%
“…It has demonstrated that it is more than just a compilation of machine learning algorithms [109]. DP can be applied to various types of robots [110], including mobile robots, manipulators, and humanoid robots. DP can be used for tasks.…”
Section: Statementioning
confidence: 99%